Manajemen Pengorganisasian Program Kursus Markaz Bahasa Arab Darul Lughah Waddirasat Islamiyah - Islahel Umam; Moh. Hasin; Zakiyah Arifa (An Nabighoh Jurnal Pendidikan Dan Pembelajaran Bahasa Arab, 2019)
This research discusses about: 1) organizing management in Arabic center DLWI Pamekasan, 2) problems in organizing management at Arabic center institute DLWI Pamekasan. This is a descriptive qualitative research. The data are collected by interviews and documentation. Then the data were analyzed in three steps, 1) data reduction, 2) data presentation, 3) drawing conclusions / verification. The results of this research shows that the organizing management Arabic language center DLWI Pamekasan arrangged the division of duties and authority of members of the organization based on structure namely linear organization. Authority is not given to just anyone but through a strict qualification system.